Cost benefit analysis tool for climate smart agricultural practices/technologies - International Fund for Agricultural Development; CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Cost-Benefit Analysis (CBA) tool is used to determine the relative profitability of alternative cropping practices, involving the comparison of the annual flow of incremental net benefits with that of incremental costs